The Effect of miR-4800 Restoration on Proliferation and Migration of Human Breast Cancer Cells In Vitro - Monireh Khordadmehr; Reyhaneh Matin; Behzad Baradaran; Elham Baghbani; Farinaz Jigari-Asl; Saeed Noorolyai (Tabriz University of Medical Sciences, 2023)
Purpose: MicroRNAs (miRNAs) can contribute to cancer initiation, development, and progression. In this study, the effect of miRNA-4800 restoration on the growth and migration inhibition of human breast cancer (BC) cells was investigated. Methods: For this purpose, transfection of miR-4800 was performed into MDA-MB-231 BC cells using jetPEI. Subsequently, the expression levels of miR-4800 and CXCR4, ROCK1, CD44, and vimentin genes were measured using quantitative real-time polymerase chain reaction (q-RT-PCR) and specific primers. Also, the proliferation inhibition and apoptosis induction of cancer cells were evaluated by MTT and flow cytometry (Annexin V-PI method) techniques, respectively. Additionally, cancer cell migration after miR-4800 transfection was assessed by wound-healing (scratch) assay. Results: The restoration of miR-4800 in MDA-MB-231 cells resulted in the decreased expression level of CXCR4 (P ˂ 0.01), ROCK1 (P ˂ 0.0001), CD44 (P ˂ 0.0001), and vimentin (P ˂ 0.0001) genes. Also, MTT results showed restoration of miR-4800 could significantly reduce cell viability rate (P ˂ 0.0001) compared with the control group. Cell migration remarkably inhibited (P ˂ 0.001) upon miR-4800 transfection in treated BC cells. Flow cytometry data demonstrated that miR-4800 replacement considerably induced apoptosis in cancer cells (P ˂ 0.001) compared with control cells. Conclusion: Taken together, it seems that miR-4800 can act as a tumor suppressor miRNA in BC and play an essential role in modulating apoptosis, migration, and metastasis in BC. Therefore, it may be suggested as a potential therapeutic target in treating BC by performing additional tests in the future.